Role of Monoclonal Antibodies in the Treatment of Asthma - Paul M O’Byrne (Canadian Respiratory Journal)
BACKGROUND: Patients with severe refractory asthma represent a small subset of the asthmatic population (between 5% and 10% of all patients) but are the greatest burden to the health care system. New treatment approaches developed to manage some of the phenotypes of severe refractory asthma have included humanized monoclonal antibodies (hMabs).